Error monitoring in a distributed system - Nykänen, Paavo (2024)
While the concept of distributed systems encapsulating and isolating functionalities and errors inside their services is a great benefit for a system, it can also introduce various problems. One of these drawbacks is that if an error occurs in one of the services, the rest of the system is not aware of it and the error might go unnoticed. This would delay fixing it and allow the same error to keep repeating and causing issues. This problem is addressed in this thesis by creating and applying an error monitoring framework for a single service of a distributed system. The framework is supposed to monitor for different kinds of errors in the target service and its resources. When these metrics notice errors, they should be indicated to the developers or system admins in different ways like notifications or visually on a monitoring dashboard. The framework is also tested by applying it to Akamon Innovations' Dataplatform system's Timeseries service and measured against various need statements given by Akamon.